The influence of evaluation through ludic activities to improve the vocabulary in EFL students - Granizo Sampedro, Karina Alejandra (2025)
This study, entitled “The Influence of Evaluation through Ludic Activities to Improve the Vcabulary in EFL Students” has as objective to determine the contribution of ludic activities when they are used as an evaluation strategy to improve the English as a Foreign Language vocabulary at 2° of Bachillerato General Unificado “A” at “San Felipe Neri” Highschool in Riobamba City in the academic period 2024-2025. A quantitative approach with applied and descriptive levels was employed for the development of the research, which contributed to understand how ludic activities advantage a better vocabulary evaluation when applied and executed within the English classroom environment. The study population consisted on the 39 students of 2° of Bachillerato General Unificado “A” at “San Felipe Neri” Highschool. The questionnaire was used as technique, and pre-test and post-test as instruments of data collection. The results of the present study indicate that, in the pre-test, performed previous the application of the strategy, a low level was evident on most of the learners. However, in the post-test, developed after the execution of the strategy, it was verified that most of the students improved significantly their lexicon level. Finally, the positive impact of the use of ludic activities to evaluate the vocabulary of the English students was demonstrated because with the help of this tool, scholars can increase their lexicon and subsequently improve their English level.